The Potential And Challenges Of Decision Support Systems For Islamic Banking And Finance - Othman bin Abdullah; Amir bin Shaharuddin; Muhamad Azhari bin Wahid; Mohd. Shukor bin Harun (University of Turin, 2024)
Non-Indexed Publication